Multiple cranial tuberculomas with meningitis and miliary tuberculosis in an immunocompetent adult - Ahmet Doğan; Hasan Tahsin Gözdaş; Tayibe Bal; Sultan Beste Şahin (Northwestern Medical Journal)
Miliary brain tuberculosis (TB) is a rare and highly lethal clinical form resulting from the extensive lymphohematogenous spread of Mycobacterium tuberculosis. Widespread brain involvement often suggests immunosuppression. However, cases have been reported in immunocompetent adults. Prognosis depends largely on prompt diagnosis and initiation of treatment. This case report presents an immunocompetent adult with miliary pulmonary TB diagnosed by bronchoalveolar lavage (BAL) fluid analysis and diffuse brain tuberculomas on brain magnetic resonance imaging (MRI).